Kinomic profiling of glioblastoma cells reveals PLCG1 as a target in restricted glucose - Kiera Walker; Nathaniel H. Boyd; Joshua C. Anderson; Christopher D. Willey; Anita B. Hjelmeland (BMC, 2018)
Abstract Background For glioblastoma (GBM) treatments to be effective in vivo, understanding the effects of the tumor microenvironment is imperative. In traditional cell culture conditions, glucose concentrations do not model physiologic levels, nor the diminished concentrations found in tumor niches. We therefore sought to profile the differences in kinase activity in GBM cells cultured in restricted glucose to identify pathways that could be targeted with small molecule inhibitors. Methods Using the PamStation12 platform, we examined the ability of GBM lysates from cells cultured in standard or low glucose conditions to phosphorylate 144 tyrosine and 144 serine/threonine peptides that correspond to known protein phosphorylation sites. Potential kinase targets were identified and validated using small molecule kinase inhibitors in GBM spheroid cultures. Results Using results from two GBM patient-derived xenografts, we determined common changes to peptides derived from Phospholipase C, Gamma 1 (PLCG1) and Raf-1. Using PLC and Raf inhibitors, we found a significantly stronger growth inhibitory effect of the PLC inhibitor U73122 under restricted glucose conditions. In contrast, Raf inhibitors were significantly growth inhibitory regardless of the nutrient level tested. Conclusions Together, our data demonstrate that kinase activity is altered in low glucose conditions and that kinomic profiling can assist with the identification of effective strategies to target GBM growth. Our data further suggest the importance of accurately modeling the tumor microenvironment to reproduce cancer cell signaling and develop drug screens for anti-cancer agents.